Demystifying Literacy Disparities: The Interplay of Economic Conditions and Educational Spending - Yangailo, Tryson (Journal of Developing Economies, 2025)
This study provides a comprehensive analysis of the interplay between literacy rates, GDP per capita, and government spending on education in different regions of the world. Using secondary data from the World Bank and Jamovi software for statistical analysis, the study reveals significant disparities in literacy rates. Europe and Central Asia (excluding high-income countries) have the highest literacy rates, while Sub-Saharan Africa and Central Europe and the Baltics have comparatively lower rates. The results of the correlation analysis show a weak linear relationship between GDP per capita and literacy rates, while a non-linear relationship indicates a stronger relationship. Government spending on education shows a moderate positive correlation with literacy rates, but the results of regression analysis reveal inefficiencies, suggesting that increased spending does not always translate into improved literacy outcomes. The study addresses gaps in the existing literature by challenging the simplistic view that higher economic growth and spending automatically improve literacy, and by highlighting the need for more targeted education policies.